Perception Analysis of Digital-Based Accounting Implementation in MSMEs Through TAM, UTAUT and DOI Approaches - Handriyani Dwilita; Pipit Buana Sari; M. Irham Ardiansyah S (International Journal of Economics, Management and Accounting, 2025)
Accounting information is needed for economic decision making obtained from the accounting process. Currently, there are various accounting applications and preparation of digital-based financial statements, but their use is still small. This study uses three approaches to the theory of perception of technology, namely TAM, UTAUT and DOI. This type of research is descriptive qualitative. The research data is primary data collected through questionnaires and interviews. The number of responses was eight MSME business people in Klambir Lima Kebun village. The results revealed that respondents had positive perceptions of the usefulness and benefits of using technology, but negative perceptions for ease of use. MSME business actors in Klambir lima village argue that digital technology-based accounting can only be applied to businesses that are larger than the businesses they are currently running. And it will be easy for those who have an accounting education background. However, business actors are willing to try to use it if it is supported by the surrounding community who also uses it and there is assistance from related parties, government, and academics.